Uji Pengaruh Pestisida Nabati Menggunakan Ekstrak Daun Sirsak (Annona muricata) terhadap Walang Sangit (Leptocorisa oratorius) - Vika Maulida (Bioscientiae, 2022)
Vegetable pesticides are chemical compounds derived from plants that are used to eradicate Plant Destruction Organisms (OPT) in the form of pests and plant diseases as well as plant pests (weeds). Walang sangit (Leptcorisa oratorius F.) is a nuisance insect or pest that often damages cultivated plants. This pest can damage almost all types of plants. The purpose of testing vegetable pesticides using soursop leaf extract (Annona muricata) is to determine the effectiveness of vegetable pesticides using the extract method from soursop leaves (Annona muricata) against rice bugs (Leptocorisa oratorius F.) on rice plants. The application of different concentrations of botanical pesticides (60 ml/L, 70 ml/L, and 90 ml/L) and different treatments, namely in the morning, afternoon and evening. The results obtained were in treatment A1 with a concentration of 60ml/liter died faster than other treatments and concentrations. The uneven death of walang sangit can be caused by several things such as age differences, lack of oxygen, as well as food and drinks available in plastic cups.